Writers and Writing in Southeast Asia - Arinto, Patricia; Darma, Budi; Deriada, Leoncio; Evasco, Marjorie; Gonzalez, NVM; Ong, Charlson; Sugbo, Victorio (Journal of English Studies and Comparative Literature; Vol 6 No 1 (2000))
none